Review of Indian Dasyproctus Lepeletier & Brullé 1835 (Hymenoptera: Crabronidae) with description of four new species - Binoy, C.; Kumar, P. Girish; Santhosh, S. (Zootaxa, 2021)
The Indian species of the genus Dasyproctus Lepeletier & Brullé (Crabroninae: Crabronini: Crabronina) are reviewed resulting in the descriptions of four new species viz., D. attenboroughi, D. leclercqi, D. niger, and D. tsunekii. Keys to both sexes of Indian Dasyproctus are provided. Comparisons within D. buddha (Cameron) and D. agilis species groups allowed the withdrawing of Crabro (=Dasyproctus) idrieus Cameron from synonymy and raising D. agilis orientalis (Cameron) to full species status. Dasyproctus amplicarinalis Yue & Ma, 2021 is synonymized with D. idrieus (Cameron, 1901) and D. hainanensis Yue & Li, 2021 with D. geethae Binoy & Girish Kumar, 2021.